Does the animacy of the antecedent play a role in the production of relative clauses? - Lobo, Maria; Vaz, Stéphanie (Matraga - Revista do Programa de Pós-Graduação em Letras da UERJ, 2017)
In previous studies that included elicited production and comprehension tasks (Costa, Lobo and Silva 2011), it has been shown that there is a high discrepancy between the rates of production of subject relative clauses vs. object relative clauses both in children and adults, but the two groups differed qualitatively. In the comprehension task, adults performed very well, unlike children, who had trouble with object relative clauses. This points to a specific difficulty with structures that involve intervention (Friedmann, Belletti and Rizzi 2009). In the present study, we investigated the role of animacy features of the antecedent in the production of object relative clauses, and specifically whether the production of object relatives would be higher with inanimate antecedents. Previous studies have mentioned the animacy features of the arguments as relevant (Corrêa 1994; Goodluck 2005; Kidd et al. 2007; Durrleman, Bentea and Guasti 2016). We explore the relevance of the findings for the discussion on the nature of the asymmetry between subject and object relative clauses. We analyze data from a spontaneous production corpus of a young European Portuguese speaking child that confirm that object relatives often have inanimate antecedents. We also conducted an elicited production task, inspired on Novogrodsky and Friedmann 2006, which elicited relative clauses manipulating the animacy of the antecedent. 42 European Portuguese children aged 4 to 6 participated in this task, as well as a control group of 20 adults. Results from the elicited production task show a higher production of object relatives with inanimate antecedents in both groups, although the difference was only significant for the adults. We conclude that the animacy of the antecedent is a feature that may play a role in the production of relatives. --------------------------------------------------------------------------------- A ANIMACIDADE DO ANTECEDENTE DESEMPENHA UM PAPEL NA PRODUÇÃO DE ORAÇÕES RELATIVAS? Em estudos anteriores que incluíram tarefas de compreensão e de produção induzida (Costa, Lobo and Silva 2011), mostrou-se que há uma assimetria considerável entre as taxas de produção de orações relativas de sujeito e de objeto, quer nas crianças, quer nos adultos, mas os dois grupos apresentaram diferenças qualitativas. Na tarefa de compreensão, os adultos tiveram um desempenho muito bom, ao contrário das crianças, que tiveram dificuldade com orações relativas de objeto. Estes resultados suportam a hipótese de que há uma dificuldade específica com estruturas que envolvem intervenção (Fried mann, Belletti and Rizzi 2009). No presente trabalho, investigamos o papel de traços de animacidade do antecedente na produção de relativas de objeto, mais especificamente, investigamos se a produção de orações relativas de objeto aumenta com antecedentes não animados. Trabalhos anteriores mencionaram a relevância dos traços de animacidade dos argumentos (Corrêa 1994; Goodluck 2005; Kidd et al. 2007; Durrleman, Bentea and Guasti 2016). Exploramos a relevância destes resultados para a discussão sobre a natureza da assimetria entre orações relativas de sujeito e de objeto. Analisamos dados de produção espontânea de uma criança falante de português europeu que confirmam que a maioria das orações relativas de objeto produzidas pela criança têm antecedentes não animados. Aplicamos ainda uma tarefa de produção induzida, inspirada em Novogrodsky and Friedmann 2006, que induzia a produção de orações relativas manipulando a animacidade do antecedente. Participaram na tarefa 42 crianças falantes de português europeu com idades entre os 4 e os 6 anos e um grupo de controlo de 20 adultos. Os resultados mostram que existe uma produção de relativas de objeto mais elevada com antecedentes não animados, ainda que a diferença tenha sido significativa apenas no grupo dos adultos. Concluímos que a animacidade do antecedente é um fator que desempenha um papel na produção de relativas. --- Artigo em inglês. --- DOI: http://dx.doi.org/10.12957/matraga.2017.28710